Comparison of the Accuracy of Bracket Placement with Height Bracket Positioning Gauge and Boone Gauge - Amir Mohammadi; Seyed Hossein Moslemzadeh (Tabriz University of Medical Sciences, 2011)
Background and aims. Diverse gauges have been used to measure and determine bracket height for correct bracket positioning. The aim of the present study was to determine and compare bracket positioning accuracy by using height bracket positioning gauge (HBPG) and Boone gauge (BG). Materials and methods. Nineteen sets of stone models were prepared from one patient. One set was employed to determine the ideal position of brackets, and the remaining nine pairs of sets for bracket placement by nine clinicians using HBPG and BG. Teeth were then sectioned from the stone models and placed inside acrylic molds; photographs were taken and imported to a computer. In two groups, the position of each bonded bracket was compared in three aspects of vertical, mesiodistal and angular with the ideal position of every bracket. Finally, bracket positioning errors were measured. Results. Mann-Whitney U test demonstrated significant differences in the means of vertical error between the HBPG group and BG groups (P<0.001), while there were no significant differences between mesiodistal and angular errors. Factorial ANOVA revealed that gauge and tooth type, and the position of tooth on the right and left side of the mouth play a major role in the rate of vertical error. Conclusion. Vertical accuracy of bracket positioning by the use of HBPG is more than that by BG. However, there is no difference between two gauges in relation to the mesiodistal and angular errors.